THE INFLUENCE OF INDUSTRIAL JOB PRACTICES ON THE READINESS OF STUDENTS IN ENTERING THE JOB MARKET FOR CLASS XII IN CONSTRUCTION ENGINEERING COMPETENCY PROGRAM IN STATE VOCATIONAL HIGH SCHOOL 1 PALANGKA RAYA ON ACADEMIC YEAR 2018/2019 - Januar Mampe Maradona Panjaitan; Wiratno (Jurusan Pendidikan Teknologi Dan Kejuruan, 2020)
During Entering the 21st century, the globalization is more intensive than previous era for competition in the job market since confidently observed nowadays. In similar side, it is unpredictable and fluctuated following by market demand and market trend. Innovation and creativity are very necessary as the example of this phenomenon in development of science and technology. Some of them can be directly observed such as newest brand of domestic products, innovative services, communication modes, attitudes in communication, the delivery services, and so on. Therefore, the role of Vocational School is being crucial to give the output with standard qualification of alumnus who have experienced on job training in real industrial workplaces. Industrial Job Practices are part of the Dual System Education (PSG) as a joint program between Vocational High Schools and the Business World/Industrial World (DU/DI). The existence of industrial practice, will provide insight and knowledge to students about the real job markets. In addition, by the existence of Industrial Job Practices, students can apply the theories that have been obtained in formal class beforehand to shape their basic and intermediate industrial skills. Based on this background, this study aims to investigate and find out t how Industrial Job Practices might influence the student readiness in entering the real job field and job market by students in Class XII of Building construction engineering competency program in SMK Negeri 1 Palangka Raya at academic year 2018/2019. This research adopts the quantitative-descriptive study where is conducted at SMK N 1 Palangka Raya From 17 May 2019 to 11 June 2019. It is about 69 students of class XII Building Construction Engineering Field Program which is consisting ofrespectively 20 students majoring in Brick and Concrete Construction Engineering, 17 students majoring in Wood Construction Engineering, 32 students majoring in Civil Drawing Engineering. The technique of collecting data implements a closed questionnaire method (questionnaire) while the instrument validity test was carried out in class XII construction engineering competency Program at SMK Negeri 1 Palangka Raya using construct validity. The results of the instrument validity test produces 40 as the valid statement items and 0 being invalid statement which is counted to 40 instruments. In this research, the reliability testing applies Cronbach alpha formula that is followed by the descriptive data analysis technique. The research results showed that there is about 79.87% effecting the readiness of students entering the job field in the Department of Brick and Concrete Construction Engineering as the high category. Nonetheless, it is around 78.38% and 78.85% respectively for students of Wood Construction Engineering program positioning the high category as well.